Clinical and genetic characteristics of distal arthrogryposis caused by mutations in the PIEZO2 gene - T. V. Markova; E. L. Dadali; S. S. Nikitin; A. F . Murtazina; O. L. Mironovich; I. V. Kanivets (Нервно-мышечные болезни)
Mutations in the PIEZO2 gene, which is involved in the formation of the mechanosensitive cation channel Piezo2, can cause distal arthrogryposis type 3 (Gordon’s syndrome), type 5, and Marden–Walker syndrome. Clinical and genetic characteristics of two patients with distal arthrogryposis with autosomal dominant inheritance and one with autosomal recessive inheritance are presented. Exome sequencing in one case revealed a de novo mutation in exon 52 of the PIEZO2gene c.8238G>A (p.Trp2746*, NM_022068.3), in the second, a known deletion of three nucleotides in exon 52 of the PIEZO2 gene c.8181_8183delAGA (p Glu2727del, NM_022068.3) was found, in the third, two mutations in the compound heterozygous state – a deletion of four nucleotides leading to a shift in the reading frame in c.1863_1866delTCAG(p.Ser621fs, NM_022068) and a deletion with putative coordinates 10785050–10789339 bp, spanning 15–16 exons of the PIEZO2 gene (NM_022068; LOD 2.40). The third patient was found to have two newly detected mutations in the compound heterozygous state – a deletion of four nucleotides, leading to a shift in the reading frame in exon 14, p.1863_1866delTCAG (p.Ser621fs, NM_022068) and a deletion with assumed coordinates 10785050–10789339 b. o., (NM_022068; LOD 2.40), spanning 15–16 exons of the PIEZO2 gene. The previous assumption was confirmed that heterozygous mutations are more often localized in exon 52 of the PIEZO2 gene and disrupt the amino acid sequence of the C‑terminal region of the protein molecule, while in patients with an autosomal recessive mode of inheritance of the mutation, the N‑terminal region is more often found.